A Systematic Development Methodology for Mixed-Mode Behavioral Models of In-Vehicle Embedded Electronic Systems. (13th December 2009) - Muller, Candice; Valle, Maurizio; Prodanov, William; Buzas, Roman
Abstract : The rising demands for safety, power-weight reduction, and comfort make the in-vehicle network of embedded electronic systems very complex. In particular system reliability is essential, especially because of the safety requirements. Test and verification of the entire in-vehicle network by means of behavioral simulations are each time more widely adopted. To this aim, behavioral models that faithfully represent the behavior of mixed-mode-embedded systems are essential for achieving reliable simulation results. This paper presents a systematic development methodology for mixed-mode behavioral models of in-vehicle-embedded systems. The methodology allows achieving accurate models, which provide reliable system simulations. The model development methodology is described and the results of the methodology applied to two case studies are presented: (1) the mixed-mode behavioral model of a generic Flexray physical layer transceiver and (2) the mixed-mode behavioral model of a CAN bus transceiver-integrated circuit. The simulation results show that behavioral simulations are much faster than transistor level simulations. Moreover, behavioral simulations are flexible, which allows quickly changing and verifying the communication network topology if compared with hardware prototypes.